WAYS TO IMPROVE INNOVATIVE MECHANISMS OF ANTI-MONOPOLY CONTROL - Abdiyev, Alimardon Chorshanbayevich; Bekbutayev, Nodirjon Fayzullayevich (THE INNOVATION ECONOMY, 2026)
The article analyzes the issues of improving antitrust control based on innovative mechanisms. It is argued that platform markets, network effects and algorithmic management in the digital economy have a significant impact on the competitive environment. The study considers the possibilities of using HHI and concentration coefficients in assessing market concentration. It also highlights the importance of antitrust control mechanisms based on digital monitoring, Big Data and artificial intelligence. The results of the study show that innovative approaches serve to increase the effectiveness of competition protection and reduce monopoly risks.